A clinical evaluation of efficacy and safety of cefepime monotherapy versus piperacillin-tazobactam in patients of paediatric age group with febrile neutropenia in a tertiary care centre of north India. (July 2016) - Aamir, Mohammad; Abrol, Pankaj; Sharma, Deepak; Punia, Harish
Objective: To evaluate clinically the efficacy and safety in northern India of cefepime monotherapy versus piperacillin-tazobactam in patients of paediatric age group with febrile neutropenia. Material and Methods: Children aged ≤18 years admitted febrile with chemotherapy-induced neutropenia were randomised into two groups comprising 20 cases in each group viz. CEF (receiving cefepime only) and PIP-TAZO (receiving piperacillin-tazobactam). Based on clinical and laboratory tests, patients were classified into: microbiologically documented infections (MDI); clinically documented infections (CDI); and unexplained fever (UF). They were assessed for clinical signs and symptoms as well as laboratory parameters at the time of enrolment and subsequently on days 3 and 7. Results: Incidence of MDI, CDI and UF were 22.5%, 47.5% and 30%, respectively. The mean duration of neutropenia (in days) was 5.45 ± 2.1 in the PIP-TAZO group and 5.5 ± 1.5 in the CEF group ( P  = 0.305). The success rate defined as clearing infection effectively and improvement of neutropenia was comparable ( P  = 0.705). There was a mortality rate of 20% in the PIP-TAZO group as compared to 10% in the CEF group. Conclusion: We conclude that cefepime monotherapy and piperacillin-tazobactam are equally efficacious and safe in treating patients with febrile neutropenia. Empirical monotherapy with cefepime would prevent an unnecessary extra economic burden as well as avoiding the serious adverse or toxic effects of multi-drug regimes, especially in low- and middle-income countries.